Observation of itinerant ferromagnetism and coupled magnetoresistance in a spinel CuCo2S4. Issue 28 (25th June 2021) - Yue, Zengji; Hou, Zhiqian; Yun, Frank; Liu, Peng; Yang, Guangsai; Bake, Abdulhakim; Zhao, Weiyao; Cortie, David; Shu, Chaozhu; Hu, Shaojie; Cheng, Jipeng; Wang, Xiaolin
Abstract : A novel ferromagnetic spinel CuCo2 S4 T c ∼ 125 K was discovered. The ferromagnetism originates from Co and Cu atoms, and leads to a positive magnetoresistance in the paramagnetic regime, and a cross-over in the ferromagnetic regime. Abstract : We report the existence of ferromagnetism in the thiospinel compound CuCo2 S4 with T c ∼ 125 K. The magneto-electronic transport of the CuCo2 S4 demonstrates a metallic conductivity and positive magnetoresistance at high temperature. At low temperature, in the ferromagnetic state, there is evidence of spin-transport coupling with magnetic domains giving a region of negative magnetoresistance near the coercive field. The electronic band structure of CuCo2 S4 was calculated using density-functional theory (DFT), which shows a ferromagnetic metallic state, in agreement with experiment. With nickel doping, both the spinel CuCo1.5 Ni0.5 S4 and CuCoNiS4 display paramagnetism down to the lowest measured temperature (3 K). This indicates that, as in other itinerant magnetic sulfides, the exchange interactions are highly sensitive to electron/hole doping. The tunable magnetism in the spinel CuCo2 S4, together with its high conductivity, suggests that this thiospinel material could be a candidate for spintronic applications.